Induced sensitivity of Bacillus subtilis colony morphology to mechanical media compression - Polka,Jessica; Silver,Pamela A (PeerJ PrePrints, 2014)
Bacterial from several taxa, including Kurthia zopfii, Myxococcus xanthus, and Bacillus mycoides, have been reported to align growth of their colonies to small features on the surface of solid media, including anisotropies created by compression. While the function of this phenomenon is unclear, it may help organisms navigate on solid phases, such as soil. The origin of this behavior is also unknown: it may be biological (that is, dependent on components that sense the environment and regulate growth accordingly) or merely physical. Here we show that B. subtilis, an organism which typically does not respond to media compression, can be induced to do so with two simple and synergistic perturbations: a mutation that maintains cells in the swarming (chained) state, and the addition of EDTA to the growth media, which further increases chain length. EDTA apparently increases cell length by inducing defects in cell separation, as the treatment has only marginal effects on the length of individual cells. These results lead us to three conclusions. First, the wealth of genetic tools available to B. subtilis will provide a genetically tractable chassis for engineering compression sensitive organisms in the future. Second, the sensitivity of colony morphology to media compression in Bacillus is a physical rather than biological phenomenon dependent on a simple physical property of rod-shaped cells. And third, colony morphology under compression holds promise as a rapid, simple, and low-cost way to screen for changes in the length of rod-shaped cells or chains thereof.
Keywords: mechanotaxis; elasticotaxis; Bacillus mycoides; Bacillus subtilis; chain length; EDTA; swarming